تاثير تمرينات التعلق بالسلالم الثابته في تطوير القوة الخاصه وفقا لمساحه نشاط بعض العضلات الذراعين لدى لاعبي الجودو - سعاد عبد حسين; ليزا رستم يعقوب (الرياضة المعاصرة, 2015)
Introduction and the importance of research: The basics of the development of the technical level of the Games sports in general and judo , in particular, focus on capacity -related skill that should be developed , where is the sport wrestling judo and one of the sports that have received in recent years, with great interest in the field of research and studies , which helped to get many developments in the field of athletic training and preparation methods judo wrestlers numbers based on a sound scientific basis for the development of physical abilities and strength are the most important elements of fitness special judo player and occupies the first place among the elements of special fitness The research problem come from the Wants researchers to know the effect of exercises chains fixed to the development of special strength of the arms because most coaches are focusing on their training methods Albulayomterc in wrestling judo fact that the game needs to muscle strength and mass physical so focused on researchers to focus on those with disabilities training and improve the work of the working muscles through the upgrading of physical general and special power in particular